Evaluating latent tuberculosis testing and treatment programme for new migrants in South East England. (13th November 2019) - Paudyal, P; Mason, A; Gedi, A; Purcell, B
Abstract: Background: Tuberculosis (TB) cases in England often originate from high burden TB countries due to 'reactivation' of the latent TB infection (LTBI), an asymptomatic and non-infectious phase lasting years. 5, 137 TB cases were notified in England in 2017, and 71% of these patients were born outside the UK. This mixed-method study evaluated the implementation of the four LTBI testing and treatment programme for new migrants in South East (SE) England. Methods: A retrospective database (May 2016-Feb 2018) review was undertaken to identify LTBI cases using multiple data sources; LTBI testing laboratories, LTBI programmes, and the national TB team at Public Health England. In addition, a survey questionnaire was emailed to 51 stakeholders (45% response rate) and five in-depth interviews were conducted with LTBI programme leads/TB nurses to explore the challenges of the programme. Quantitative data were analysed using descriptive summary statistics and qualitative interviews were analysed using thematic content analysis. Results: Of the 5931 eligible patients, 40 % (n = 2391) accepted the LTBI test and 13.4% (n = 321) tested positive. 93.1% (n = 299) of the positive patients were referred for treatment and 63.8% (n = 191) of these accepted the treatment. The programme also picked up 18 active TB cases, an unexpected incidental finding. Results from the survey and the interviews identified laboratory arrangements, workforce, and data collection/management as the greatest challenges for the LTBI programme. Patient focused care, cultural understanding, success in testing/treating migrants, and raising awareness amongst professionals/communities were highlighted as achievements of the programme. Conclusions: This study found that LTBI programmes in SE England are in line with national expectations and other LTBI programmes in England. The study recognises the achievements and good practice of the LTBI teams in SE England and identifies key barriers to improve the service for the future. Key messages: Data collection and management is the biggest challenges of the LTBI programmes in SE England. The LTBI programmes in SE England are in line with national expectations.